Comparable outcomes in patients with B-cell acute lymphoblastic leukemia receiving haploidentical hematopoietic stem cell transplantation: Pretransplant minimal residual disease-negative complete remission following chimeric antigen receptor T-cell therapy versus chemotherapy - Yang, Ting-Ting; Meng, Ye; Kong, De-Lin; Wei, Guo-Qing; Zhang, Ming-Ming; Wu, Wen-Jun; Shi, Ji-Min; Luo, Yi; Zhao, Yan-Min; Yu, Jian; Jing, Rui-Rui; Zhao, Meng-Yu; et al. (Frontiers in Immunology, 2022)
Introduction Chimeric antigen receptor (CAR)-T therapy followed by haploidentical hematopoietic stem cell transplantation (haplo-HSCT) markedly improves the long-term survival of patients with refractory/relapse (R/R) B-cell acute lymphoblastic leukemia (B-ALL). Methods We performed a parallel comparison of transplant outcomes in 168 B-ALL patients undergoing haplo-HSCT after achieving minimal residual disease (MRD)-negative CR from CAR-T therapy (n=28) or chemotherapy (n=140) between January 2016 and August 2021. The chemotherapy group was further divided into the first CR group (chemo+CR1, n=118) and a second or more CR group (chemo+≥CR2, n=22). Results With a median follow-up of 31.0 months, the 2-year OS, LFS, NRM, and relapse rates in the CAR-T and chemotherapy groups did not differ significantly (OS, 87.9% vs. 71.5 %; LFS, 72.0% vs. 66.8%; NRM, 3.9% vs. 13.7%; relapse, 24.1% vs. 19.4%; respectively). Multivariate analysis confirmed that ≥CR2 at transplantation following chemotherapy was an independent risk factor associated with poor OS (HR 4.22 [95% CI, 1.34–13.293], P = 0.014) and LFS (HR 2.57 [95%CI, 1.041–6.343], P = 0.041). The probabilities of OS and LFS at 2 years in the CAR-T group were comparable to those in the chemo+CR1 group, but significantly higher than those in the chemo+≥CR2 group (OS: 87.9% vs. 37.8%, P =0.007; LFS:72.0% vs. 41.7%, P = 0.043). No significant differences in the incidence of NRM were observed among the three groups. Conclusions Our results demonstrated that patients with R/R B-ALL receiving haplo-HSCT after CAR-T therapy achieved outcomes comparable to those of patients transplanted after chemotherapy-based MRD-negative CR1, without increased risk of transplant-related mortality and toxicity.